The Effects of Sales Growth, Current Ratio, Total Asset Turnover, Debt to Asset Ratio, and Debt to Equity Ratio on the Return on Equity in Energy and Mining Companies - Muhani, Muhani; Digdowiseiso, Kumba; Prameswari, Kintan Mayang (Budapest International Research and Critics University, 2022)
This study aims to determine the effects of Sales Growth (SG), Current Ratio (CR), Total Asset Turnover (TATO), Debt to Equity Ratio (DER), and Debt to Asset Ratio (DAR) on the Return on Equity (ROE) of Energy and Mining sector companies, listed on the Indonesia Stock Exchange for the 2015-2019 period. The population in this study were 47 energy and mining companies. The sampling technique used was purposive sampling and obtained a sample of 14 companies. This study obtained the secondary data in the form of financial statements and can be accessed through www.idx.co.id. The analytical technique used in this study is linear regression of panel data using the STATA 16 program. The results showed that SG, TATO, DER, and DAR all had a insignificant effect on ROE in energy and mining companies. However, CR produced a negative and significant effect on ROE in these companies.